IMPROVING STUDENTS’ ACHIEVEMENT IN WRITING DESCRIPTIVE TEXT THROUGH MIND MAPPING STRATEGY - Jojor Saut Mandiri Padang; Busmin Gurning (Universitas Negeri Medan, 2014)
The objective of this study was to investigate whether the application of MindMapping Strategy improve the students’ achievement in writing descriptive text. Thisstudy was a classroom action research. The subject of this study was class VIII SMPSwasta HKBP Pardamean which consisted of 30 students. The study was conductedin two cycles, cycle I consisted of three meetings and cycle II consisted of threemeetings. The instruments for collecting data were quantitative data (writing test) andqualitative data (observation sheet, and questionnaire sheet). Based on writing scores,students’ score kept improving in every evaluation and based on the observationsheet, and questionnaire sheet it was found that teaching and learning process ranwell. Students could enlarge their thinking process. The result of this study showedthat Mind Mapping Strategy improved the students’ achievement in writingdescriptive text.